ADCP current measurements (1200 kHz) during RV SENCKENBERG cruise SE202103-1 - Michelle Albinus; Axel Braun; Helge-Ansgar Giebel; Claudia Thölen; Jochen Wollschläger; Thomas Henry Badewien (PANGAEA, 2025)
Ocean velocities were collected by a Teledyne RDI 1200 kHz Workhorse Sentinel II ADCP that was mounted on RV SENCKENBERG during RV SENCKENBERG cruise SE202103-1. The transducer was located at 1.2 m below the water line. The instrument was operated in single-ping, broadband mode with bin size of 0.25 m and a blanking distance of 0.25 m. The velocity of the ship was calculated from position fixes obtained by the Global Positioning System (GPS) received at a Trimble SPS461 Modular GPS Heading Receiver. Heading was obtained both from the Trimble receiver and the internal ADCP gyro. Heading as well as pitch and roll data from ADCP extquotesingles internal gyrocompass and the navigation data were used by the data acquisition software ViSea DAS (AquaVision®) internally to convert ADCP velocities into earth coordinates. Accuracy of the ADCP velocities mainly depends on the quality of the position fixes as well as Trimble receiver and internal ADCP heading data. Further errors stem from a misalignment of the transducer with RV SENCKENBERG extquotesingles centerline.